Game Artificial Intelligence: Challenges for the Scientific Community - Lara-Cabrera, Raúl; Nogueira-Collazo, Mariela; Cotta-Porras, Carlos; Fernández-Leiva, Antonio José (My University, 2015)
This paper discusses some of the most interesting challenges to which the games research community members may face in the área of the application of arti cial or computational intelligence techniques to the design and creation of video games. The paper focuses on three lines that certainly will in uence signi cantly the industry of game development in the near future, speci cally on the automatic generation of content, the a ective computing applied to video games and the generation of behaviors that manage the decisions of entities not controlled by the human player.
Keywords: Inteligencia artificial; Videojuegos; Non-player characters; Procedural; A ective Computing; Human-like behavior; Game Artificial Intelligence